Selection of natural fibre reinforced composites using fuzzy VIKOR for car front hood - Sivakumar, Dhar Malingam; Muhd Ridzuan , Mansor (Inderscience Enterprises Ltd., 2016)
Weight reduction of transportation vehicles is an important method in improving fuel efficiency, reducing energy consumption and greenhouse gas emissions. One of the solutions is through the application of green materials as substitutes to conventional engineering materials. However, the selection of a suitable substitute material for the intended application often imposes great challenges due to the variety of alternative materials to choose from as well as the need to satisfy multiple and conflicting requirements from various stakeholders. Therefore, the aim of this study is to use fuzzy VIKOR, the multiple criteria decision making method, to identify the appropriate type of natural fibre for fibre reinforced composites to be applied on the fibre metal laminate for car front hood to achieve the transportation weight reduction. The result suggested that M3 (kenaf) has the best criteria. Kenaf has been selected as the best natural fibre as it satisfies two compromise solutions. It has a least VIKOR index value υ = 0.5. The results of the fuzzy VIKOR demonstrate the potential of natural fibre to be applied on the fibre metal laminate structure as a car front hood; this which could reduce vehicle weight and subsequently reduce the overall vehicle CO2 gas emissions.